(3HdhZ GdBQGH aj dWGFa GdYJGHs - (3eMeO Hf CMeO GdebQF GdCfHGQj, TeS GdOjf, J(B857(3g` s ((3CHh GdSYhO Hf eMeO GdeGdci GdCTYQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi djS dg Chd jHOjg hdG BNQ jafjg bGd gPG GdcJGH LeYJg ef LhGgQ cd cJGH , hSejJg jTJed Ydi PcQ ef cTa dge GdMLGH s
(3BNQgG (B:s
(3MJi Cf eGdcG NGRf GdfGQ jbhd (B: (3jG eMeO eG JQcJ ddfGQ dZVH QHc ai CeJc ef HbjI hbGd Udi Gddg Ydjg hSde (B: (3Efi dCTaY jhe GdbjGeI dCcKQ eeG Ydi hLg GdCQV ef MLQ heOQ hGdg CYde s
(3HQSe CMeO Hf GdLeGdi jhSa GdYOhis
(3hYdjgG JedjcGJ cKjQIs
(3hGfXQ GdLRA GdChd HQbei (B94(3,(B95 (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs